Evoluç\~ao e projeç\~ao de longo prazo de contribuintes e beneficiários e implicaç\~oes para o financiamento da previdência social - Rogério Nagamine Costanzi; Graziela Ansiliero (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The hasty and intense process of population aging observed in Brazil should have a relevant impact on the expected evolution in the number of potential contributors and beneficiaries of the social security schemes - particularly, the social insurance schemes, with emphasis on the public pension system. Estimating the future evolution in the number of potential contributors and beneficiaries of the social insurance schemes is relevant for the medium and long-term planning of public pension policies, especially in countries where pay-as-you-go schemes predominate - such as Brazil and its General Social Insurance Regime (RGPS). These estimates are also fundamental for planning the financing of the social security system and its largest component, the social insurance system. The present study sought to estimate and analyze the evolution on the number of contributors and beneficiaries to the social security system (notably, recipients of Social Security monetary benefits, such as pensions, survival benefits and BPC/Loas). The study period covers an eleven-year interval (2012-2022), based on microdata of the Continuous National Household Sample Survey (PNAD Contínua) and administrative data pertaining to RGPS. This Discussion Paper provides projections for the ratio of contributors to social security beneficiaries, with emphasis on the social insurance beneficiaries, for 2023 to 2060.
Keywords: H55; 330; pension system; social insurance financing; contributors; social insurance beneficiaries; social insurance expenditures (pay-as-you-go schemes)